Nematic van der Waals Free-energy - Oukouiss, A.; Daanoun, A. (Journal of Scientific Research, 2009)
We develop the calculation of free energy in a nematic phase for a model of spherical particles with the long-range anisotropic interaction from the van der Waals theory. We map the gas-liquid equilibrium, which is coupled to a first-order isotropic-nematic transition. We discus how the topology of the phase diagrams changes upon varying the strengths of the isotropic and nematic interactions. Keywords: Phase diagrams; Nematic interactions; Free energy; Transitions. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2595 J. Sci. Res. 1(3), 409-421 (2009)